Changes in soil microbial community structure during long‐term secondary succession. (27th January 2020) - Liu, Jin; Jia, Xiaoyu; Yan, Weiming; Zhong, Yangquanwei; Shangguan, Zhouping
Abstract: Understanding the changes in microbial community composition that occur during succession can help elucidate the mechanisms that drive successional dynamics. However, the mechanisms underlying community assemblages and promoting temporal succession are often overlooked in microbial ecology, and comparisons of the relative roles of bacteria and fungi during long‐term secondary succession are rare. Using both 16S and ITS rRNA gene sequencing, we studied shifts in bacterial and fungal communities in a well‐established secondary successional chronosequence that spanned approximately 160 years in an ecosystem. Our results showed that the abundance of both bacteria and fungi increased with succession in the early stages but then reached a relatively stable state in later successional stages. Diversity showed a fairly linear increase with succession, and there were inconsistent changes between the bacterial and fungal communities. During succession, soil bulk density, soluble carbon, total nitrogen and plant richness had large effects on the microbial community. The abundance of most phyla showed parabolic trends with succession; however, Verrucomicrobia and Basidiomycota showed linear increases with succession, and Cercozoa and Chytridiomycota showed linear decreases with succession. These microbial taxa may be considered collaborative development microbial biomarkers of secondary succession. The predicted microbial functions related to C and N cycle genes showed corresponding changes in succession, which need further study. Our findings suggest that the relationships between soil physicochemical properties and microbial communities mutually influence one another, leading to their ongoing relationship in the course of secondary succession.